2020
DOI: 10.3390/ma13225071
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of Swelling Pressure for Superabsorbent Polymer and Soil Mixtures

Abstract: Superabsorbent polymers (SAPs) are used in agriculture and environmental engineering to increase soil water retention. Under such conditions, the swelling pressure of the SAP in soil affects water absorption by SAP, and soil structure. The paper presents the results of swelling pressure of three cross-linked copolymers of acrylamide and potassium acrylate mixed at the ratios of 0.3%, 0.5% and 1.0% with coarse sand and loamy sand. The highest values of swelling pressure were obtained for the 1% proportion, for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 50 publications
2
13
0
Order By: Relevance
“…Misiewicz et al [77] proposed a model that may be used to determine the theoretical swelling pressure generated in loamy sand soil and coarse sand. It is the first version of the model and has a fixed soil type and bulk density, although it allows modification of the concentration of superabsorbent polymer or the choice of a superabsorbent polymer with suitable granulation.…”
Section: Soil Water Characteristicmentioning
confidence: 99%
See 2 more Smart Citations
“…Misiewicz et al [77] proposed a model that may be used to determine the theoretical swelling pressure generated in loamy sand soil and coarse sand. It is the first version of the model and has a fixed soil type and bulk density, although it allows modification of the concentration of superabsorbent polymer or the choice of a superabsorbent polymer with suitable granulation.…”
Section: Soil Water Characteristicmentioning
confidence: 99%
“…Differences in the quantity of water retained between freely swelling samples and samples swelling under a load reached up to 94% [75]. In relation to the swelling pressure generated [77], certain types of SAP have a significant impact on soil bulk density and porosity, the effects of which have been described by Han et al [78] and Bai et al [79]. In the case of SAP application in relatively large amounts, changes can be observed in the values of soil shear strength or hydraulic conductivity [80].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, systematic laboratory experiments are beginning to unravel the origins of these conflicting results. One factor that is now appreciated to play a key role is the pressure experienced by the SAP inside soil: in real-world applications, SAP swelling upon contact with water is highly dependent on the local pressure [3,27,28]. Indeed, SAP absorption of water has been shown to be dramatically reduced upon simply loading a SAP-soil mixture with a top layer of soil, due to the increased pressure inside [29].…”
Section: Introductionmentioning
confidence: 99%
“…Given these gaps in knowledge, here, we built on our previous studies [3,27,28] to characterize how the addition of SAP to soil changes its coefficient of permeability over time, which is a novel approach, and how these dynamics depend on SAP grain size and soil grain size. We found that even small amounts of SAP can dramatically decrease the soil permeability, in some cases even causing complete blockage of water infiltration that can have important consequences in real-world settings.…”
Section: Introductionmentioning
confidence: 99%